Metode Dan Media Promosi Kesehatan Terhadap Perubahan Perilaku Pengobatan Penderita TB Paru Di Wilayah Puskesmas Putat Jaya Kota Surabaya - Hari Kristianto; Muhammad Badira; Anto; Asriwati (2019)
Pulmonary Tuberculosis is still a world health problem, where the World Health Organization (WHO) reports that most of the world's population is stricken with this disease, mostly in developing countries, estimated in Indonesia. Efforts to control pulmonary TB are carried out nationally with the DOTS (Directly Observed Treatment Shourt Course), this program is a direct monitoring of short-term treatment. The type and design of the research used in this study were experimental with the pattern of posttest-only control group design. The number of samples in the study were 27 people each group, so the number of respondents was 54 people. The results of the study using the Mann Whitney test showed that the knowledge variables of Tuberculosis sufferers were assessed by the average rating of 32.48 and the ranking control group an average of 22.52 with a difference in the delta value of 9.96, while the value of ρ was 0.016 . On the attitude variable of pulmonary tuberculosis patients the average treatment group is 31.48 and in the ranking control group an average of 23.52 with a difference in the value of delta 7.96, while the value of ρ value is 0.061